Нові верифіковані знахідки гриба Camarosporidiella celtidis (Shear) Thambug., Wanas. & K.D. Hyde на Ulmus laevis Pall. в Україні - Новгородський, А.А.; Novgorodsky A.А. (Івано-Франківськ : Супрун В.П., 2023)
As a result of the critical revision of two herbarium specimens collected on elm branches in Ukraine, which were previously identified as Hendersonia ulmea, another fungal species – Camarosporidiella celtidis was recognized
New verified records of the fungus Camarosporidiella celtidis (Shear) Thambug., Wanas. & K.D. Hyde on Ulmus laevis Pall. from Ukraine
Keywords: гриби; біорізноманіття; ДНК; баркодинг; Національний природний парк "Гетьманський" (Сумська область, Україна)